Human interaction with the environment in the Red Sea : selected papers of Red Sea Project VI - Agius, Dionisius A.; Khalil, Emad.; Scerri, Eleanor.; Williams, Alun (Middle East and Islamic Studies E-Books Online, Collection 2017, ISBN: 9789004325999., 2017)
This volume contains a selection of fourteen papers presented at the Red Sea VI conference held at Tabuk University, Kingdom of Saudi Arabia in 2013. It sheds light on many aspects related to the environmental and biological perspectives, history, archaeology and human culture of the Red Sea, opening the door to more interdisciplinary research in the region. It stimulates a new discourse on different human adaptations to, and interactions with, the environment. With contributions by Andre Antunes, K. Christopher Beard, Ahmed Hussein, Emad Khalil, Solène Marion de Procé, Abdirachid Mohamed, Ania Kotarba-Morley, Sandra Olsen, Andrew Peacock, Eleanor Scerri, Pierre Schneider, Marijke Van Der Veen and Chiara Zazzaro.